2023
DOI: 10.1101/2023.07.31.549902
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Elucidating the role of muscarinic acetylcholine receptor (mAChR) signaling in efferent mediated responses of vestibular afferents in mammals

Anjali K. Sinha,
Choongheon Lee,
Joseph C. Holt

Abstract: The peripheral vestibular system detects head position and movement through activation of vestibular hair cells (HCs) in vestibular end organs. HCs transmit this information to the CNS by way of primary vestibular afferent neurons. The CNS, in turn, modulates HCs and afferents via the efferent vestibular system (EVS) through activation of cholinergic signaling mechanisms. In mice, we previously demonstrated that activation of muscarinic acetylcholine receptors (mAChRs), during EVS stimulation, gives rise to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 116 publications
1
5
0
Order By: Relevance
“…We measured VsEP waveforms at +6 dB re: 1.0 g/ms before and aser the IP administraPon of 2mM Oxo-M. Consistent with previous findings (Sinha et al, 2023), we observed an increase in P1N1 amplitude over Pme in both control and KCNQ3 KO mice following Oxo-M administraPon (Fig. 7E).…”
Section: Vsep In Kcnq3 Ko Micesupporting
confidence: 91%
See 4 more Smart Citations
“…We measured VsEP waveforms at +6 dB re: 1.0 g/ms before and aser the IP administraPon of 2mM Oxo-M. Consistent with previous findings (Sinha et al, 2023), we observed an increase in P1N1 amplitude over Pme in both control and KCNQ3 KO mice following Oxo-M administraPon (Fig. 7E).…”
Section: Vsep In Kcnq3 Ko Micesupporting
confidence: 91%
“…We next wanted to explore the effect of mAChR activation of on VsEP metrics in KCNQ3 KO mice. Previous research (Sinha et al, 2023) demonstrated that the activation of mAChRs using Oxotremorine-M (Oxo-M), a mAChR agonist, enhanced VsEP P1N1 amplitude and reduced P1 latency in control mice (Sinha et al, 2023). Here, we repeated this experiment in KCNQ3-KO mice.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations